Hybrid cryptography with a one-time stamp to secure contact tracing for COVID-19 infection - El-Douh, Ahmed Abdel-Rahim; Lu, Song Feng; Elkouny, Abdelatif A.; Amein, A.S. (Zielona Góra: Uniwersytet Zielonogórski)
The COVID-19 pandemic changed the lives of millions of citizens worldwide in the manner they live and work to the so-called new norm in social standards. In addition to the extraordinary effects on society, the pandemic created a range of unique circumstances associated with cybercrime that also affected society and business. The anxiety due to the pandemic increased the probability of successful cyberattacks and as well as number and range. For public health officials and communities, location tracking is an essential component in the their efforts to combat the disease.
Keywords: hybrid cryptography; digital signature; hash; RSA; AES; asymmetric cryptography; symmetric cryptography; cybersecurity; COVID-19